Microstructural Features of Freezing and Thawing-Creep Damages for Concrete Mixed with Fly Ash - Bing Li; Lian-ying Zhang; Ming Li; Hai Pu; Chao Ma; Pei-tao Qiu (Geofluids)
The macroscopic morphology characteristics, pore structure characteristics, and microfracture morphology of concrete with fly ash subjected to the freeze-thaw-creep effect were analyzed via scanning electron microscopy (SEM). The results revealed that the macrosection of a specimen subjected to freeze-thaw cycling evolves from a regular to an irregular morphology in which the degree of fragmentation increases. Four specimen pore structure types characterized by single holes, nonconnected hole clusters, connected hole clusters, and fly ash holes, respectively, were identified. The microfracture morphology of the concrete was found to include five types of brittle fractures—river, step, cascade, hemispherical, and irregular patterns—and two types of ductile fractures—dimple and peak forest patterns. Two sets of experiments in which (1) the fly ash content (m=35%) was kept constant and the number of freeze-thaw cycles increased, and (2) the number of freeze-thaw cycles (n=120) was kept constant, and the fly ash content was increased were carried out. In both cases, the number of connected hole clusters increased and a surrounding skeleton structure with a needle filamentous or flaky appearance was produced. In addition, the degree of deterioration of the pore structure increased and the fracture features changed from brittle to ductile.